Sustainable Synthesis of Silver Nanoparticles Using Plant-Based Waste Biomass for the Removal of Cationic Dyes-A Review - Parlayıcı, Şerife (Fine Chemical Engineering, 2024)
Silver nanoparticles (AgNPs) have been the subject of researchers due to their unique properties such as optical, antimicrobial, and electrical properties depending on size and shape. This review focuses on their green synthesis of nanoparticles, metal nanoparticles and mainly AgNPs. Green chemistry synthesis method has attracted great attention as an alternative method in recent years because it is more energy efficient, safer and less toxic. At the same time, this study gives a general idea about the preparation of AgNPs by green synthesis method using lignocellulosic biomass. One of the main uses of lignocellulosic wastes in a circular economy is to introduce renewable resources into the market and on the other hand, to promote the valorization of waste. Moreover, lignocellulosic raw materials expand the sustainability possibilities of industrial processes as a result of their low cost and low environmental impact. On the other hand, dyes, which are wastes from different industries such as textile, plastic, food and paper, are the main cause of water pollution. This study provides a detailed investigation of the removal performance of AgNPs obtained using different lignocellulosic biomass for environmentally harmful cationic dyes.